PENGUATAN KAPASITAS MASYARAKAT ADAT DALAM PENGELOLAAN EKONOMI BERBASIS AWIG-AWIG DI DESA ADAT BUALU, KABUPATEN BADUNG, PROVINSI BALI - Putu Ratna Windusara Putri; I Made Sujana; Yoviniani Yevri Yanseni; Fitria Asri Satria Dewi (Nusantara Hasana Journal, 2023)
This community service activity aims to increase the capacity of indigenous communities in managing local economic potential through the utilization of customary laws (adat awig-awig) in Bualu Traditional Village, Badung Regency, Bali Province. The rapid development of the tourism sector requires indigenous communities to have the ability to manage economic opportunities sustainably without neglecting cultural values ​​​​passed down from generation to generation. The activity was carried out through socialization, training, focus group discussions, and mentoring for traditional village officials, MSMEs, youth groups, and community leaders. The results of the activity showed an increase in participants' understanding of the function of awig-awig in supporting community economic management, strengthening local economic institutions, and increasing community capacity in developing businesses based on local potential. This activity contributes to increasing community participation in sustainable village economic development.